Evaluation of the Bacillus cereus strain 1-p protease for the unhairing of goatskins during leather production - Nyakundi, Joseph Ondari (Array, 2020)
The unhairing stage of leather processing is associated with the production of significant amounts of solid and liquid wastes. The use of enzymes to replace the polluting sulphides currently used for unhairing is a viable alternative. Various proteases from different Bacillus cereus strains as well as many other bacterial strains have been used successfully for the unhairing of skins. However, no previous work has assessed the use of the crude alkaline protease extract from Bacillus cereus strain 1-p, a novel Bacillus cereus strain obtained from the shores of Lake Bogoria - a soda lake in Kenya – in the unhairing of goatskins. This study, therefore, evaluates the potential of the protease extract from the Bacillus cereus strain 1-p to unhair goatskins. Optimum variables for unhairing using the protease were investigated. Complete unhairing was achieved within 12 hours at 27°C and pH 12 using the crude enzyme. The period and temperature required for complete unhairing were significantly lower than that of other enzymatic unhairing techniques. Compared to the leather unhaired with sulphide, the leather unhaired with the enzyme did not only show superior organoleptic properties but also recorded comparable or superior physical properties, namely tensile strength (26.94 N/mm2), percentage elongation (76.29%), tear strength (43.59 N/mm), and distension at grain crack and burst (7.9 mm and 8.2 mm respectively). The wastewater from the enzymatic unhairing process recorded a significant reduction in biochemical oxygen demand (78%), chemical oxygen demand (83%), and the wastewater volume (50%) compared to the process that uses sulphide. It was concluded that the use of the crude protease extract from the Bacillus cereus strain 1-p in unhairing goatskins is feasible.